2008
DOI: 10.1111/j.1349-7006.2008.00982.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of transient receptor potential melastatin 7 channel induces cell death in gastric cancer

Abstract: CaAmong ion channels, the transient receptor potential (TRP) melastatin 6 and 7 channel is similarly permeable to both of the dominant divalent cations Ca 2+ and Mg 2+ .(4) TRP channels were first cloned from the Drosophila species (TRP and transient receptor potential-like protein) and constitute a superfamily of proteins that encode a diverse group of Ca 2+ -permeable nonselective cation channels.(5) The TRP family is divided into three subfamilies: classic, vanilloid (TRPV), and melastatin type (TRPM).(5) T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
126
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 124 publications
(137 citation statements)
references
References 50 publications
9
126
0
Order By: Relevance
“…Mazzone et al (2011) suggested that Changes in Ca 2+ -activated Cl -conductances expression in ICCs may directly contribute to human diabetic gastroparesis. However, Kim et al (2008) suggested TRPM7 has an important role in gastric cancer cell death. The exact functions of TRPM7 and Ca 2+ -activated Cl -conductances in GI tract need to be investigated in future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mazzone et al (2011) suggested that Changes in Ca 2+ -activated Cl -conductances expression in ICCs may directly contribute to human diabetic gastroparesis. However, Kim et al (2008) suggested TRPM7 has an important role in gastric cancer cell death. The exact functions of TRPM7 and Ca 2+ -activated Cl -conductances in GI tract need to be investigated in future.…”
Section: Discussionmentioning
confidence: 99%
“…TRPM7 has been suggested to have a central role in cellular Mg 2+ homeostasis (Schmitz et al, 2003), in central nervous system ischemic injury (Aarts et al, 2003), in skeletogenesis in zebrafish (Elizondo et al, 2005), in the defecation rhythm in Caenorhabditis elegans (Vriens et al, 2004), in cholinergic vesicle fusion with the plasma membrane (Brauchi et al, 2008), in phosphoinositide-3-kinase signaling in lymphocytes (Sahni et al, 2008), in cell death in gastric cancer (Kim et al, 2008), in osteoblast proliferation (Abed et al, 2009) and in breast cancer cell proliferation (Guilbert et al, 2009). But, until now, the effect of the 5-LOX inhibitors, NDGA, AA861 and MK886 on these TRPM7 several physiological functions have not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [9] reported that human gastric adenocarcinoma cells express TRPM7 channel and that this channel is essential for cell survival. In addition, they suggested that this channel be viewed as a potential target for the pharmacological treatment of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we found that human gastric adenocarcinoma (AGS) cells express the transient receptor potential melastatin 7 (TRPM7) channel, which is known to be essential for cell survival and has been suggested as a pharmacological target for the treatment of gastric cancer [9]. Therefore, we investigated whether waixenicin A influences AGS cell survival.…”
Section: Effects Of Waixenicin a On Ags Cellsmentioning
confidence: 99%
See 1 more Smart Citation